A Low-Complexity PAPR Reduction for Space-Time Block Code MIMO-OFDM by using modified-PTS with ABC-Concurrent Algorithm - Pitchaya Boontra; Tanairat Mata; Pisit Boonsrimuang (My University, 2019)
One of the problems of using Orthogonal Frequency Division Multiplexing (OFDM) technique is the higher Peak-to-Average Power Ratio (PAPR) which leads to the fatal degradation of the system performance in the non-linear channel.To solve this problem, the partial transmit sequence (PTS) was proposed for Space-Time Block Code (STBC) with Multi-Input and Multi-Output (MIMO)-OFDM as STBC MIMO-OFDM system which can reduce the PAPR effectively.However, its complexity in the PAPR reduction process becomes higher in proportion to the increase of its considered cluster number.To solve this problem, this paper proposes a low-complexity PAPR reduction by using the modified-PTS with artificial bee colony (ABC) and concurrent algorithm as ABC-Concurrent algorithm for STBC MIMO-OFDM system which can improve better PAPR with low-complexity and can perform better Bit-Error-Rate (BER) in the non-linear channel.The silent features of the proposed modified-PTS with ABC-Concurrent algorithm are to reduce the PAPR with decreasing side information (SI) to half by modifying PTS with the concurrent algorithm and to reduce the complexity in PAPR reduction process by applying ABC algorithm for STBC MIMO-OFDM system.From the various results by using computer simulation, it can be confirmed that the proposed modified-PTS with ABC-Concurrent algorithm can reduce PAPR by approximately 3.4 and 0.4 dB at CCDF 10 -3 as comparing with the original STBC MIMO-OFDM and conventional PTS methods respectively, and can use the complexity approximately only 19% in PAPR reduction process which is decreased a lot from using the conventional PTS method.Moreover, the proposed method can perform the better BER in the non-linear channel than the original STBC MIMO-OFDM and the conventional.PTS methods which is close to that of operating in nonlinear channel.
Keywords: Spacetime block code; Code (set theory); PAPR reduction in OFDM